The Post-Plebiscite Conflict of 1982 and non-humanitarian intervention in Sardauna local govertment are of Taraba State, Nigeria - Kingsley, Joseph Bonglo; Suffian Mansor; Azlizan Mat Enh (Penerbit Universiti Kebangsaan Malaysia, 2023)
After about two decades, since the United Nations plebiscite of 1961, in the former British Cameroons, the long enjoyed peaceful and cordial clime eluded the Mamilla Plateau Sardauna Local Government Area (LGA) of Taraba State, Nigeria. The main objective of this study is to examine why and how the post-plebiscite conflict of 1982 failed to receive humanitarian intervention from the relevant agencies. The work examines the nature of the post-plebiscite conflict of 1982. Furthermore, it discusses the roles of the three tiers of government (Local, State, and Federal). The study adopts the qualitative-cum-historical methodology and uses primary and secondary data sources. The primary data sources comprised oral interviews, a report of the Judicial Commission of Inquiry, and archival materials. Secondary sources included journals, newspapers, conference papers, dissertations, and theses. The research findings revealed that the conflict was more inter-ethnic than political between the Mambilla and Panso/Kambu ethnic groups. It uncovered that besides the security intervention, the three tiers of government failed to make any modicum of humanitarian intervention towards the Panso/Kambu who were the Internally Displaced Persons (IDPs) and the refugees who fled into the Republic of Cameroon for safety. In conclusion, the study suggests that since the Mambilla, the three tiers of government, and relevant agencies were liable, compensation and written apologies should be tendered to the IDPs and the refugees or their respective communities as a way of genuine reconciliation and a true mark of healing the wounds of the past.